Analysis, design and development of web-based thesaurus manager prototype for Philippine medical thesaurus administrator component - Cepillo, Kinchan D.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
The world of medicine is a vast repository of information designed to help the lives of people. And medical professionals in the Philippines that include doctors, nurses, medical technicians, and the likes are exposed on a daily basis to various medical terms. The Philippine Medical Thesaurus is an attempt for medical terms to be stored, organized and managed.
This study focused on the analysis, design, and the development of web-based thesaurus manager prototype particularly on the administrator component.
The research provided the requirements for a web based thesaurus manager prototype. These requirements were then used to formulate a design for the manager prototype, and out of the design, developed the components essential for the thesaurus manager prototype. and also, documents namely an installation manual, administrator component manual and technical documentation were produced.
Thus, the thesaurus manager prototype contains modules for term management, volume management, other administration and extension modules for administrator and extension modules for administrator such as menus and Content Management System (CMS) modules like user administration, and permissions.
Recommendation were made to further improve the administrator component of the thesaurus manager prototype such as the comprehensive testing, further development by hooking it to applications in need of a thesaurus manager as component, further development to enhance usability and functionalities and production testing over the Internet and Institute of Library and Information Science (ILIS) Local Area Network (LAN). Other recommendations were testing of other software engines, use of different scripting language, and use of other web application development tools.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Computer software; Internet (computer network) in medicine